Blastocrithidia-A Genetic Alien from the Planet Earth - Lukeš, Julius; Čapková Pavlíková, Zuzana; Yurchenko, Vyacheslav; Paris, Zdeněk; Valášek, Leoš Shivaya (Cold Spring Harbor perspectives in biology, 2025)
The standard genetic code, which applies almost without exception, is the key to our understanding of molecular biological processes. Although it is close to impossible to imagine that sparse code changes occur naturally given proteomic constraints, specific cases of codon usage alterations have been documented, mostly in unicellular eukaryotes. Here, we summarize what we have learned about Blastocrithidia, a little-known parasitic flagellate with all three stop codons reassigned to sense codons, which uses UAA as the only universal stop codon. We first describe its origin, life cycle, morphology, cultivation, and transformation, the combination of which predisposes it to become the first tractable eukaryote with a noncanonical genetic code. Next, we present our across-the-genome analysis revealing uneven distribution of in-frame stops and discuss the features distinguishing in-frame and genuine stop codons that allow for so-called position-specific termination. Finally, given what is known about stop codon readthrough by near-cognate transfer RNAs (tRNAs) and the fidelity of stop codon recognition by eukaryotic release factor 1 (eRF1), we propose a model illuminating how unique properties of Blastocrithidia tRNAs, combined with specific alterations of its eRF1, enable this massive deviation from the standard genetic code.
Keywords: terminační kodon; Euglenozoa; Země (planeta); RNA, Transfer; genetický kód; Codon, Terminator; Genetic Code; RNA transferová; Earth, Planet